PENGEMBANGAN POTENSI KELOMPOK WANITA TANI UNIT PEMUKIMAN TRANSMIGRASI PULAU MALAN KABUPATEN KATINGAN PROVINSI KALIMANTAN TENGAH - IIS - YUANITA; LISNAWATY SILITONGA; PAULINI - (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
The purpose of this activity was to develop small industries of animal products at transmigration sites bywomen’s empowerment. The rural women could improve not only the animal products such as meats, eggs, seedsof duck and chicken, but also local and regional income. In addition to improving the ability of rural women inbusiness by utilizing commodity Alabio and chicken as a superior product. When animal products processinginto food products, it could provide high economic value and benefits up to 100%. This Community Service wascarried out for 8 months from March to October 2012 in UPT Pulau Malan Katingan. The methods consistedof 1) Socialization and counseling to educate the partner group (women farmers group) about Alabio Ducksand Native Chicken farming, accompanied by the demplot of both animal, 2) Training and demonstration ofanimal products such as egg shredded (egg abon), cracker scrabbed and organic manure, and3) Evaluation andmonitoring. Establishment of women farmers group in two partner area was the first result of this activity. Theprogram activities, socialization,demonstration demplots, training and monitoring have a very good responsefrom the partners as well as being inspiration to promote and develop the potential of the group.Implementationof Alabio ducks and native chickens farming succeed to improve the productivity in terms of quantity(number oflivestock and bodyweight) and quality(body health andvitality of animals). The animal products processing suchas egg shredded (egg abon), cracker scrabbed and organic manure also create new revenue sources for the groupof partners.Keywords: Women Farmers Group, UPT PulauMalan, DucksAlabio, Native Chicken, Processed Products